STOCK RETURNS IN THE DIGITAL ERA: SUSTAINABILITY AND FINANCIAL PERFORMANCE OF JAKARTA ISLAMIC INDEX COMPANIES - Ilma Mufidatul Firdaus; Datien Eriska Utami (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2026)
Stock returns are a key indicator considered by investors in evaluating investment performance, particularly in the Islamic capital market. Growing attention to sustainability issues and rapid digitalisation has further influenced investor behaviour toward Sharia-compliant instruments. This study examines the effect of Environmental, Social, and Governance (ESG) performance and financial indicators, Return on Assets (ROA) and Tobin’s Q on the stock returns of firms listed in the Jakarta Islamic Index (JII) during 2020–2024. It also investigates the moderating role of digital transformation. A quantitative approach is employed using panel data regression analysis with the Fixed Effect Model. The sample is selected through purposive sampling, resulting in 15 firms observed over five years, yielding 75 observations. Moderated Regression Analysis (MRA) is applied to assess the moderating effect of digital transformation. The findings indicate that ESG and ROA do not have a significant impact on stock returns, whereas Tobin’s Q shows a positive and significant effect. Digital transformation does not moderate the relationship between ESG, ROA, Tobin’s Q, and stock returns. This study contributes to the literature by integrating ESG, financial performance, and digital transformation within the context of the Islamic capital market, particularly the Jakarta Islamic Index, which remains relatively underexplored.